1996
DOI: 10.1021/jm950827h
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Programmed Polyamine Analogue Antidiarrheals

Abstract: The design, synthesis, and testing of a novel class of antidiarrheal drugs based on a tetraamine pharmacophore are reported. While N1,N14-diethylhomospermine (DEHSPM) (5 mg/kg) completely prevents diarrhea in rodents, tissue distribution studies demonstrated that the principal metabolite of DEHSPM, homospermine (HSPM), accumulates and persists in tissues for a protracted period of time. This accumulation accounts for a large part of the chronic toxicity of DEHSPM. Thus a major objective was to develop a metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 26 publications
3
64
0
Order By: Relevance
“…[21] Purescine derivatives have been used as antimalaria [22] and antiplasmodic agents. [23] This kind of polyamines has also been found to be important in other fields of current research, for example, metabolism [24] and biogenesis, [25] antibiotics, [26] coagulation inhibitors, [27] antidiarrhoics [28] and cytostatics. [29] The two-step hydroaminomethylation/hydrolysis procedure has been used so far to synthesize chiral amino alcohols with low Mw (Scheme 2 and Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…[21] Purescine derivatives have been used as antimalaria [22] and antiplasmodic agents. [23] This kind of polyamines has also been found to be important in other fields of current research, for example, metabolism [24] and biogenesis, [25] antibiotics, [26] coagulation inhibitors, [27] antidiarrhoics [28] and cytostatics. [29] The two-step hydroaminomethylation/hydrolysis procedure has been used so far to synthesize chiral amino alcohols with low Mw (Scheme 2 and Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…This emergent area of research could be applied for the study of new modulators of histamine and polyamine metabolism with potential pharmaco-logical interest. This is the case of previously described metabolically programmed polyamine analog antidiarrheals [67].…”
Section: Systemic Approaches For the Study Of Polyamine And Histaminementioning
confidence: 92%
“…[87] It has been shown that certain PA analogues can act, for example, as antiparasitic [88] and antimalarial [89] agents, and as antidiarrhoeals. [90] Thus, DEHSPM is already under clinical evaluation to control chronic diarrhoea, in particular associated with AIDS patients, whereas a new class of metabolically unstable, to avoid accumulation of cytotoxic metabolites, PA antidiarrhoeals (e.g. 38, Figure 10) has been recently developed by Bergeron et al [90] Macrocyclic polyamines, such as the bicyclams IPS31 [91] or JM 3100 ( Figure 10) [92] or their complexes with metals, e.g.…”
Section: Polyamine Analogues Involved In Other Cellular Functionsmentioning
confidence: 99%
“…[90] Thus, DEHSPM is already under clinical evaluation to control chronic diarrhoea, in particular associated with AIDS patients, whereas a new class of metabolically unstable, to avoid accumulation of cytotoxic metabolites, PA antidiarrhoeals (e.g. 38, Figure 10) has been recently developed by Bergeron et al [90] Macrocyclic polyamines, such as the bicyclams IPS31 [91] or JM 3100 ( Figure 10) [92] or their complexes with metals, e.g. IPS32, [91] have been found effective against HIV-1 and HIV-2, acting as fusion inhibitors.…”
Section: Polyamine Analogues Involved In Other Cellular Functionsmentioning
confidence: 99%
See 1 more Smart Citation